SAT0265 Clinical characteristics of systemic lupus erythrematosus in an egyptian population: a retrospective cohort. (15th June 2017) - Medhat, B; Hadidi, T El; Hadidi, K El; Yousri, A; Hassan, D; Talaat, F; Maged, L; Shabaan, M; Eissa, M; Gobashy, N Hamdy El; Sobhy, N; Baki, N Abd El; et al.
Abstract : Background: Systemic lupus erythrematosus (SLE) is an autoimmune disease with a myriad of manifestations, that could vary among different ethnic and racial groups. Objectives: To study the prevalence of various manifestations of SLE in an Egyptian population. Methods: Information in this study was derived from the medical records of SLE patients who followed up in a private clinic in Cairo from January 1980 to June 2016. Results: This descriptive retrospective case series included 1109 juvenile (19.4%) and adult (80.6%) patients, of which 114 (10.3%) were males and 995 were females (89.7%). Age of onset showed a mean of 26±11.19 years, and the mean of disease duration was 48.78±58.46 months (median: 26 years). The most common manifestations were synovitis (76.7%), malar rash (48.5%), leukopenia (45.7%), and photosensitivity (45.6%). At least one of the antiphospholipid antibodies was present in 41.8% of the patients tested for APL (636 patients). However thromboembolic manifestations and/or recurrent fetal loss occured in 11.5% of the patients. Neuropsychiatric manifestations were evident only in 6.4% of the patients, with seizures being the most common neuropsychiatric manifestation, present in 4% of the patients. 33.1% of the patients had nephritis, which followed the onset of the disease by a mean duration of 20±21.3 months (median=12 months). There were gender differences in the disease characteristics. Cutaneous vasculitis, nephritis, and hypocomplementemia were statistically higher in males (p=0.012, p=0.01, and p=0.041 respectively). Whereas, synovitis, and alopecia were statistically higher in females (p=0.012 and p=0.006 respectively). Patients with juvenile onset had a statisticaly higher frequency of nephritis (0=0.01), seizures (p=0.012) haemolytic anemia (p=0.001), and hypocomplementinemia (p=0.02). Conclusions: Synovitis and malar rash were the most common manifestations in our study. Secondary antiphospholipid was present in 11.5% of the patients. Male patients and juvenile patients showed a tendency towards a more severe disease. Disclosure of Interest: None declared